Optymalizacja wag w modelu średniej ruchomej ważonej - Szanduła, Jacek (Weights Optimization in Weighted Moving Average Model, 2007)
The paper presents a way to optimize weights in weighted moving average model. The minimum of the ex post forecasts mean-square error was chosen as a criterion of optimization. The author also presents the way of estimating ex ante forecasts errors. They are useful both for evaluating the admissibility of forecasts calculated with the use of estimated models and for calculating forecasts confidence intervals.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 64-76